2011
DOI: 10.1051/0004-6361/201015635
|View full text |Cite
|
Sign up to set email alerts
|

Nature vs. nurture in the low-density environment: structure and evolution of early-type dwarf galaxies in poor groups

Abstract: We present the stellar population properties of 13 dwarf galaxies residing in poor groups (low-density environment, LDE) observed with VIMOS at VLT. Ages, metallicities, and [α/Fe] ratios were derived within an r < r e /2 aperture from the Lick indices Hβ, Mgb, Fe5270, and Fe5335 through comparison with our simple stellar population (SSP) models that account for variable [α/Fe] ratios. For a fiducial subsample of 10 early-type dwarfs, we derived median values and scatters around the medians of 5.7 ± 4.4 Gyr, −… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 112 publications
3
20
0
Order By: Relevance
“…To eliminate the systematic offsets between these two models, we apply the following correction from Smith et al (2009) to adjust the values of Schiavon (2007;Sch) to the scale of Thomas et al (2003;TMB) The models of Proctor & Sansom (2002) and Sansom & Northeast (2008) are the same as that of Thomas et al (2003), except that they did not account for the [α/Fe] bias in the solar neighborhood; this, however, has negligible effects on our results. The models of Annibali et al (2007Annibali et al ( , 2011 are consistent with those of Thomas et al (2003). A more detail discussion is given in Section 3.3.…”
Section: Datasupporting
confidence: 53%
See 1 more Smart Citation
“…To eliminate the systematic offsets between these two models, we apply the following correction from Smith et al (2009) to adjust the values of Schiavon (2007;Sch) to the scale of Thomas et al (2003;TMB) The models of Proctor & Sansom (2002) and Sansom & Northeast (2008) are the same as that of Thomas et al (2003), except that they did not account for the [α/Fe] bias in the solar neighborhood; this, however, has negligible effects on our results. The models of Annibali et al (2007Annibali et al ( , 2011 are consistent with those of Thomas et al (2003). A more detail discussion is given in Section 3.3.…”
Section: Datasupporting
confidence: 53%
“…Previous studies all had relatively large uncertainties. Sansom & Northeast (2008), Smith et al (2009), andAnnibali et al (2011) obtained different slopes for this relation. Using a sample of low-mass ETGs from the Virgo Cluster, Liu et al (2016) found a [α/Fe]-σ relation with larger scatter and, based on a correlation between [α/Fe] and distance from the cluster center, concluded that low-mass ETGs are more governed by environment instead of mass.…”
Section: Introductionmentioning
confidence: 92%
“…accretion of pure stellar systems. The spectral analysis of faint companions of ETGs in low density environments, where our ETGs are mostly located, performed by Grützbauch et al (2009) showed that the vast majority of these latter do not show emission lines (see also the population analysis in Annibali et al 2011).…”
Section: Discussionmentioning
confidence: 90%
“…One of the intriguing questions in this context, particularly with respect to dwarf galaxies, is the importance of a galaxy's intrinsic properties ("nature") vs. the importance of external influences ("nurture"). Clearly, both play a role in shaping dwarf galaxies in groups and clusters (e.g., [5,25,28,29,33,42,99,100,68,69,70,71,72,126,128,162]). …”
Section: Re-ionization and Later Environmental Effectsmentioning
confidence: 99%